RETRACTED: Investigation of the root cause of subsurface damage in wind turbine gearbox bearings. (October 2016) - Li, Shu-Xin; Zhao, Peng-Cheng; Su, Yun-Shuai; Yu, Shu-Rong
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ).This article has been retracted at the request of the author. The author has requested to retract this paper as she has mistakenly used images from other researchers without asking for permission or citing their paper properly .